Update GPS Signals Spot Signs of Typhoons. - DiGregorio, B.E.
This article presents a briefs description of the COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) constellation's capabilities as a GPS based meteorological instrument. It demonstrates the predictive powers of a new technique called near-real-time radio occultation.
Keywords: COSMIC constellation; Constellation Observing System for Meteorology Ionosphere and Climate; GPS based meteorological instrument; GPS signals; Near real time radio occultation; Typhoons